Manganese oxides at different oxidation states for heterogeneous activation of peroxymonosulfate for phenol degradation in aqueous solutions - Saputra, E.; Muhammad, S.; Sun, Hongqi; Ang, Ha-Ming; Tade, Moses; Wang, Shaobin (elsevier, 2013)
A series of manganese oxides (MnO, MnO2, Mn2O3 and Mn3O4) were synthesized and tested in heterogeneous activation of peroxymonosulfate (PMS) for phenol degradation in aqueous solutions. Their properties were characterized by several techniques such as X-ray diffraction (XRD), thermogravimetric-differential thermal analysis (TG-DTA), scanning electron microscopy (SEM), and N2 adsorption/desorption isotherms. Catalytic activities of Mn oxides were found to be closely related to the chemical states of Mn. Mn2O3 is highly effective in heterogeneous activation of PMS to produce sulfate radicals for phenol degradation compared with other catalysts (MnO, MnO2, and Mn3O4). The activity shows an order of Mn2O3> MnO > Mn3O4> MnO2. Mn2O3 could completely remove phenol in 60 min at the conditions of 25 mg/L phenol, 0.4 g/L catalyst, 2 g/L PMS, and 25?C. After heat regeneration, the activity could be fully recovered. A pseudo first order model would fit to phenol degradation kinetics and activation energy was obtained as 11.4 kJ/mol.